Peran Artificial Intelligence dan Otomatisasi Sebagai Solusi Inovatif Untuk Meminimalkan Kesalahan Akuntansi - Ani Liani; Khusnul Definta; Gunawan Aji (Yayasan Cendekia Gagayunan Indonesia, 2026)
This study aims to systematically examine the role of Artificial Intelligence (AI) and automation in minimizing accounting errors while emphasizing its theoretical contribution to the growing body of AI-based accounting literature. Using a Systematic Literature Review (SLR) approach, twenty academic articles published between 2022 and 2025 were analyzed and categorized into three core themes: AI in error detection and correction, automation for reducing human error, and AI-based internal control and auditing. The findings reveal that AI technologies such as machine learning and anomaly detection are effective in identifying and correcting common accounting errors, including data entry mistakes, account misclassification, and fictitious transactions. Moreover, automation enhances operational efficiency, reduces manual workloads, supports real-time monitoring, and enables continuous auditing processes. Theoretically, this study strengthens the conceptualization of AI as a mechanism for accounting error mitigation rather than solely as an efficiency tool. The study concludes with a recommendation for future empirical research across industries to explore ethical integration and sustainable implementation of AI within accounting systems.